Has There Been a Revolution in Women's Work? - Tapper, Alan (John Curtin Institute of Public Policy, Curtin University of Technology, 2010)
This paper questions the common view that in the past half-century Australian women have radically changed their focus from unpaid domestic work to employed work. The common view is largely based on labour force participation rates. These rates give a deceptive picture. Actual work activity has to be tracked using figures on hours worked. This paper presents two sets of hourly figures from the Australian Bureau of Statistics, one set dating back to 1966, the other back to 1987. Neither suggests a dramatic change in women's actual work activity.